The Effect of Workload and Organizational Commitment on Employee Performance with Employee Engagement as Mediating Variable - Donna, Lisa Safirah Bella; Dinarjo Soehari, Tjiptogoro (Dinasti Publisher, 2024)
This study aims to identify and analysed the factors that influence employee performance, including: workload, organizational commitment, employee engagement at PT DBSI. The research method used is quantitative descriptive using Structural Equation Modelling Partial Least Square (SEM-PLS). The population in this study is 167 permanent employees of CBG BMS (Business Management & Support) division. The sample used was 118 employees, the sampling used in this study is Purposive Sampling and has filled in 45 questionnaire question items distributed online. The finding of this study show that the workload and organizational commitment has a direct positive and significant effect on the employee engagement and employee performance. Employee engagement directly has a positive and significant impact on employee performance and is able to play a role in mediating the workload and organizational commitment to employee performance. The contribution of this research is that the research findings can be used as a basis of meaningful employee performance improvement policies to support business sustainability.